Decisive Conditions for an Effective and Efficient Multi-modal Freight Transport Network in Europe: A Meta-Analytic Perspective - Kostas Bithas; Peter Nijkamp (Tinbergen Institute, 1997)
The paper addresses the issue of intermodality in European transport policy. Its aim is to derive critical factors for an effective and efficient multimodal freight transport network in Europe. The results of a survey among European transport experts are presented, while a new meta-analytic technique - roughset analysis - is deployed to infer testable conclusions.
Keywords: 330; Verkehrsinfrastruktur; Güterverkehr; Netzwerk; Europa